Protective Effects of the Polyphenolic-Rich Fraction of Cornsilk against Oxidative Stress in Streptozotocin-Induced Diabetic Rats - Hamzah, Nurraihana; Safuan, Sabreena; Wan Ishak, Wan Rosli (Jurnal Gizi dan Pangan, 2023)
Diabetes Mellitus (DM) has become a significant public health problem worldwide and primarily correlated to hyperglycaemia and abnormal lipid and antioxidant levels. Fruit and vegetable wastes are rich in phenolic compounds thus suitable for antioxidant sources. Cornsilk (CS), a maize cultivar waste, also contains phenolic compounds. The current study investigated the anti-hyperglycemic and antioxidative properties of the Phenolic-Rich Fraction of Cornsilk (PRF-CS) in Streptozotocin (STZ)-induced diabetic rats. Five groups of 30 male Sprague Dawley rats were employed in this study. A sample size of six rats each is placed in five groups: Normal-Control (NC), Diabetic-Control (DC), Diabetic-PRF-CS treated 100 mg/kg (DPRF100) and 200 mg/kg (DPRF200), and Diabetic-Metformin Treated (Dmet) groups. The PRF-CS was administered at 100 and 200 mg/kg doses for 28 consecutive days to the diabetic rats. Treatment with both doses of PRF-CS (DPRF100 and DPRF200) significantly decreased the blood glucose levels of the rats (p<0.05). Additionally, the PRF-treated rats demonstrated significantly decreased (p<0.05) lipid peroxidation (3.60±0.23 and 3.31±0.56 µmol/g, respectively). The hepatic antioxidant enzyme activities of Superoxide Dismutase (SOD) (169.35±4.75 and 175.30±3.69 U/mg, respectively), Catalase (CAT) (1457.51±152.74 and 2011.99±396.96 U/mg), and Glutathione Peroxidase (GSH-Px) (63.43±2.99 and 78.47±4.51 U/mg) were also elevated in contrast to the DC group. Furthermore, the PRF-CS administration improved the histological alterations in the liver tissues of the DPRF100 and DPRF200 rats. In conclusion, PRF-CS treatment exhibited protective effects in the diabetic rat model by decreasing oxidative stress and preserving liver integrity.